Análise teórica e experimental do comportamento térmico de um forno elétrico - Malheiros, Fernando Costa (2013)
This study investigates the thermal behavior of an electric oven under theoretical and experimental conditions. Initially, it is dedicated to building an experiment which reects the everyday use of a household electric oven and which makes it possible to gather information on the development of temperatures for oven walls and for the sample being heated. Such thermal behavior is evaluated and used to calculate radiation and convection heat ow rates applied to each of the sample\'s faces. Afterwards, an opposite problem which is minimized (optimized) by means of a genetic algorithm whose objective is to estimate the pattern of the radiation and convection ow rate calculated is proposed. The Temperatures results for each of the surfaces of the oven\'s and sample\'s are presented. The ow rates, on the other hand, are presented in terms of their convection and radiation components, and the total ow rate, which is the sum of both of them, for each of the sample\'s surface. An estimate for the opposite problem is presented alongside the total ow rate calculated from the temperatures of the experiment. The oven managed to apply a uniform temperature to the surface of the samples, although at rates lower than the ones set up. The opposite problem showed satisfactory results for the optimization of ovens. Since it only requires temperatures from the surface of the sample to be measured, the procedure for the calculation of optimal ow rates turns out to be simpler because it aims at achieving heat uniformity. However, the use of criteria for the determination of the properties and for the construction of the thermal model is required.